Modelling and optimization of enhanced coalbed methane recovery using CO2/N2 mixtures. (1st October 2019) - Fan, Chaojun; Elsworth, Derek; Li, Sheng; Chen, Zhongwei; Luo, Mingkun; Song, Yu; Zhang, Haohao
Highlights: Injection of gas mixture (CO2, N2 ) can reduce CO2 emission and enhance CBM recovery. A fully coupled thermo-hydro-mechanical model is developed to explore gas mixture ECBM recovery. The evolution of key parameters is investigated by proposed model. The recovery schedules are optimized among constant- and variable-composition injections. Abstract: Injection of gas mixtures (CO2, N2 ) into coal seams is an efficient method to both reduce CO2 emissions and increase the recovery of coalbed methane. This process involves a series of complex interactions between ternary gases (CH4, CO2, and N2 ) co-adsorption on coals, mass transport of two-phase flow, together with heat transfer and coal deformation. We develop an improved thermo-hydro-mechanical (THM) model coupling these responses for gas mixture enhanced CBM recovery (GM-ECBM). The model is first validated, and then applied to simulate and explore the evolution of key parameters during GM-ECBM recovery. Schedules of constant- and variable-composition injection are optimized to maximize CH4 recovery and CO2 sequestration. Result shows that the injected gas mixture displaces CH4 through competitive sorption and accelerates the transport of CH4 within the coal seam. The consistency between the modelling and field results verifies the feasibility and fidelity of the THM model for effective simulation key processes in GM-ECBM. Permeability evolution is strongly influenced by the combined effects of CH4 desorption induced matrix shrinkage, CO2 /N2 adsorption induced matrix swelling, thermal strains, and compaction induced by changes in effective stress. During ECBM, reservoir permeability first increases due to pressure depletion and CH4 desorption, then dramatically decreases due to matrix swelling activated by the arrival of the CO2 /N2 mixture. CH4 pressure decreases rapidly at early time due to displacement by the injected gas mixture, and then deceases slowly in the later stage. The sweep of N2 accelerates CH4 desorption and subsequent transport, and hence promotes a decrease in reservoir temperatures distant from the injection well even prior to the arrival of CO2 . CH4 production rate during GM-ECBM exhibits a decline-increase-decline trend and usually has an elevated but delayed CH4 production peak compared to primary recovery. A higher CO2 Langmuir strain constant reduces the critical CO2 composition in the injected mixture when reaching the threshold of well shut down. An improved balance between early threshold (N2 ) and large matrix swelling (CO2 ) can be achieved by injection beginning with low CO2 composition and following with a sequential increase of CO2 composition. In studied cases, the gas recovery ratio of the optimal variable-composition case reaches 68.4% compared to of 59.4% pure CO2 and 64.2% of optimal constant-composition cases, indicating a higher efficiency of variable-composition injection.